Pengembangan Sistem Aquaponik Pada Budidaya Ikan Integratif Sebagai Upaya Peningkatan Pendapatan Petani - Abdul Mukhlis Ritonga; Masrukhi; Mustaufik (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Aquaponics is an agricultural system that combines fisheries cultivation and plant cultivation, especially vegetables without soil media (hydroponics). By choosing aquaponics, we will be able to harvest 2 crops at once, namely fresh fish and vegetables. The general purpose of this service activity is to introduce to the community, especially the Jangkarbelet Fish Farmer group about integrated agriculture such as aquaponics. The specific aim is to maximize the vacant land around the pond so that it is more productive and not slum and to help the community's economy, especially the Fish Farmer group by applying aquponics by harvesting fresh fish and vegetables. This activity was carried out for 8 months at the Jangkarbelet Fish Farmer Group Grumbul Takom RT 09/02, Karanggintung Village, Sumbang District, Banyumas Regency. This aquaponic technology community service activity uses the consulting method. The activity in this method is an approach, then counseling, training and coaching is given and finally there is ongoing evaluation and monitoring from the program implementer. The results of the activity show that the application of integrated agriculture through aquaponics technology can be accepted by partner groups. There is an increase in the knowledge and skills of group partners, especially regarding aquaponics technology and this PKM program is able to help the economy of the Fish Farmer group from the results of integrated fish and vegetable cultivation.